Language and Action : a reassessment of Speech Act Theory. - Marcondes de Souza Filho, Danilo (John Benjamins Publishing Company, 1985)
This work consists of an examination and revision of some of the main theses of Speech Act Theory in relation to the problem of ideology and action-guiding language. Starting from the idea that linguistic philosophy must take into account how the social structure of the linguistic community may influence and direct the way its language is used, a critical method of analysis is proposed, developing Speech Act Theory in a way suitable for this purpose. The main guideline of this proposal is the consideration that a theory of action rather than a theory of meaning should be taken as central in th.